Restorasi Embung Sebagai Ekowisata dan Inovasi Olahan Anti Covid-19 â€œBiluluheâ€ Sebagai Upaya Memulihkan Stabilitas Ekonomi Desa - Yantu, Irwan; Bokingo, Agus Hakri (Univeristas Negeri Gorontalo, 2020)
This activity aims to (1) educate the community regarding the potential of the village that is owned and can be used as a source of income in encouraging the community's economy, (2) Developing the potential of an embung to become an ecotourism location, (3) Providing training on innovative processing of cassava and freshwater fish to be utilized a traditional anti-Covid-19